Internet of Things at the Service of Bioconstruction - Corredor-Sanchéz, Fabián Ricardo; González-Sanabria, Juan Sebastián; Mendoza-Moreno, Miguel Ángel (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The Internet of Things (Internet of Things - IoT) approach promotes the interconnection of objects that humans use on a daily basis so that they are administered, controlled and/or monitored through telematic technologies. This paradigm has a wide field of application to support several development schemes in a variety of areas. In the case of construction, there are home automation schemes, but regarding bio-constructions, the myth of incompatibility between digitized systems and “bio” schemes exists. However, bio-constructions require aesthetic, structural, environmental and technological considerations to integrate efficient and friendly systems, contributing to a sustainable environment, generating and regulating the resources of the environment in which they are implemented. In this way, a documentary research process has been developed to determine the degree of applicability of IoT for green buildings. As a result, a set of IoT technologies was identified, which can promote the administration and control of the normatively established agents involved in a bio-construction for living spaces.